Quantitative characterization of tetraspanin 8 homointeractions in the plasma membrane. Issue 19 (15th October 2021) - Wirth, Daniel; Özdemir, Ece; King, Christopher; Ahlswede, Lena; Schneider, Dirk; Hristova, Kalina
Abstract : The spatial distribution of proteins in cell membranes is crucial for signal transduction, cell communication and membrane trafficking. Members of the Tetraspanin family organize functional protein clusters within the plasma membrane into so-called Tetraspanin-enriched microdomains (TEMs). Direct interactions between Tetraspanins are believed to be important for this organization. However, studies thus far have utilized mainly co-immunoprecipitation methods that cannot distinguish between direct and indirect, through common partners, interactions. Here we study Tetraspanin 8 homointeractions in living cells via quantitative fluorescence microscopy. We demonstrate that Tetraspanin 8 exists in a monomer-dimer equilibrium in the plasma membrane. Tetraspanin 8 dimerization is described by a high dissociation constant ( K d  = 14 700 ± 1100 Tspan8/µm 2 ), one of the highest dissociation constants measured for membrane proteins in live cells. We propose that this high dissociation constant, and thus the short lifetime of the Tetraspanin 8 dimer, is critical for Tetraspanin 8 functioning as a master regulator of cell signaling.